The Empire's War Recalled: Recent Writing on the Western Front Experience of Britain, Ireland, Australia, Canada, India, New Zealand, South Africa and the West Indies - Connor, John ca. 20./21. Jh. (History compass, 2009)
The ninetieth anniversary of the end of the First World War in 2008 was marked with the publication of a number of works in many parts of what was once the British Empire. We saw an increased output in publications on the Western Front. In Britain, the recent literature attempts to rehabilitate Douglas Haig and define the ‘learning curve’ that enabled the British army to defeat Germany in 1918. In Australia, Canada and New Zealand, the performance of their soldiers on the Western Front is seen as central to national identity and this now focuses on military success rather than sacrifice in a futile war. In India, South Africa and Jamaica, there is a renewed interest in linking the First World War to national identities based on the independence or liberation struggle. In Ireland, the Great War is seen as a shared experience that can link the Nationalist and Unionist traditions in Northern Ireland and the Republic. The article concludes that this interest in the Western Front will continue into the next decade in the lead-up to the centenary of the First World War.